Enhanced removal of cesium by potassium-starved microalga, Desmodesmus armatus SCK, under photoheterotrophic condition with magnetic separation. (August 2020) - Kim, Ilgook; Choi, Gang-Guk; Nam, Seung Won; Yang, Hee-Man; Park, Chan Woo; Seo, Bum-Kyoung; Choi, Kyoung-Min; Park, Sang-Min; Ryu, Byung-Gon
Abstract: This study investigated the feasibility of using photoheterotrophic microalga, Desmodesmus armatus SCK, for removal of cesium (Cs + ) followed by recovery process using magnetic nanoparticles. The comparison of three microalgae results indicated that D. armatus SCK removed the most Cs + at both 25 °C and 10 °C. The results also revealed that the use of microalga grown in potassium (K + )-starved condition improves the accumulation of Cs + . Heterotrophic mode with addition of volatile fatty acids (VFAs), especially acetic acids (HAc), also enhanced removal of Cs + by K + -starved D. armatus SCK; maximum removal efficiency of Cs + was almost 2-fold higher than that of cells grown without organic carbon source. The Cs + taken up by this microalga was efficiently harvested using magnetic nanoparticles, polydiallyldimethylammonium (PDDA)-FeO3 . Finally, this strain eliminated more than 99% of radioactive 137 Cs from solutions of 10, 100, and 1000 Bq mL −1 . Therefore, use of K + -starved microalga, D. armatus SCK, with VFAs could be promising means to remove the Cs from the liquid wastes. Graphical abstract: Image 1 Highlights: Microalga D. armatus can eliminate radioactive 137 Cs, even at low concentrations. Addition of VFA can significantly enhance removal capability of Cs + by microalga. Cs-containing microalgae are efficiently recovered using nano-magnetic FeO3 -PDDA. K + -starved microalga can improve removal efficiency of Cs + at 25 °C and 10 °C.